2022
DOI: 10.1098/rsos.220873
|View full text |Cite
|
Sign up to set email alerts
|

Can genomic research make a useful contribution to social policy?

Abstract: As genetic research into outcomes beyond health gathers pace, largely through the use of genome-wide association studies, interest from policy-makers has grown. In the last year, two UK reports have explored the policy implications of genomic research, one from the UK Government Office for Science and one from the Early Intervention Foundation. In this article, we explore areas of consensus between these two reports and use them to propose priorities for policy-makers as we prepare for what some have termed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…While learning about genetics has been historically thought to trigger essentialist cognitive biases (Dar-Nimrod & Heine, 2011), it now recognized as pivotal for ensuring the wider population's informed participation in democratic and societal processes (Asbury et al, 2022;Asbury & Plomin, 2013;Crosswaite & Asbury, 2019;Donovan et al, 2019Donovan et al, , 2022. A series of recent empirical studies demonstrated that an accurate understanding of human genetic variation benefits people's knowledge of mental health conditions and reduces prejudice (Donovan et al, 2019(Donovan et al, , 2022Rutherford, 2020).…”
Section: Safeguarding Polygenic Score Predictions In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…While learning about genetics has been historically thought to trigger essentialist cognitive biases (Dar-Nimrod & Heine, 2011), it now recognized as pivotal for ensuring the wider population's informed participation in democratic and societal processes (Asbury et al, 2022;Asbury & Plomin, 2013;Crosswaite & Asbury, 2019;Donovan et al, 2019Donovan et al, , 2022. A series of recent empirical studies demonstrated that an accurate understanding of human genetic variation benefits people's knowledge of mental health conditions and reduces prejudice (Donovan et al, 2019(Donovan et al, , 2022Rutherford, 2020).…”
Section: Safeguarding Polygenic Score Predictions In Educationmentioning
confidence: 99%
“…At present, the majority of public communication efforts by researchers are under-or non-funded, and they often only reach a fraction of the population (Office of Science and Technology & Wellcome Trust, 2000). While some funding agencies have started to mandate public engagement and dissemination strategies (e.g., Asbury et al, 2021Asbury et al, , 2022, achieving a fundamental change in the public opinion and interpretation of the role of genetics in education will require substantial, concerted efforts.…”
Section: Safeguarding Polygenic Score Predictions In Educationmentioning
confidence: 99%
“…This could ultimately support genuinely ‘inclusive classroom communities’ (Black-Hawkins et al, 2021 , p. 13). This discussion is highly relevant to educational genetics wherein issues of stigma and self-stigma, and also expectancy effects (Shifrer, 2013 ), need to be taken seriously (Asbury et al, 2022 ).…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Engaging and listening to children’s perceptions of the idea of DNA screening for risk of learning or behaviour difficulties requires creative approaches and a focus on how children develop their understanding of complex topics such as diversity and genomic prediction. This could potentially be supported by high quality science communication within education that is accessible from the first days of primary school (Gus, 2000 ; Litvack et al 2011 ; Cairns & McClatchey, 2013 ; Beckett, 2014 ; Armstrong et al 2017 ; Black-Hawkins et al 2021 ; Asbury et al, 2022 ). We argue that it is important, and responsible, to include children, even very young children, in consultations about the future of DNA data in the context of education.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…Eusociality, the collaborative behavior seen in social insects, stands out as one of the most remarkable features in the field of science [2]. Extensive research on the theoretical foundations of eusociality has followed Hamilton's seminal publications [3]. Genomic research has significantly contributed to addressing current challenges in understanding social evolution.…”
Section: Introductionmentioning
confidence: 99%